Chol-Dex nanomicelles: Synthesis, characterization and evaluation as efficient drug carriers for colon targeting. (February 2021) - Goyal, Preeti; singh, Mahak; Kumar, Pradeep; Gupta, Alka
Abstract: Core-shell structures obtained from amphiphilic molecules on self-assembly in a medium have emerged as an important tool in the area of biomedical sciences. Here, we have synthesized cholesteryl-dextran (Chol-Dex) amphiphiles in sufficiently high yields via conjugation of cholesteryl hemisuccinate to dextran in two different concentrations (5 and 10%). After physicochemical and spectral analysis, the nanomicelles were subjected to size measurements. DLS and TEM confirmed the formation of core-shell type of nanomicelles. Hydrophobic drug-entrapped formulations (Metronidazole and Rifampicin) displayed sustained release behaviour of drugs from them. Sustained release at neutral pH demonstrated usefulness of the non-toxic delivery system for colon specific diseases. Graphical abstract: Image 1 Highlights: Amphiphilic Chol-Dex conjugates have been synthesized in a two-step process. Self-assembly of Chol-Dex conjugates yielded nanomicellar structures. Nanocomposites exhibited excellent drug entrapment and loading efficiency. Cytocompatible nanocomposites can be used for colon specific drug delivery.